Tech meets HR does e-HRM implementation influence job satisfaction among HR employees in government agencies? - Bisnar, Kristine Marie P.; Carbonilla, Adrian U.; Macorol, Marielle Joy P.
The integration of Electronic Human Resource Management (E-HRM) Systems has reshaped HR practices across various sectors, yet its influence on employee job satisfaction in the Philippines public sector remains largely unexplored. This study investigates how E-HRM implementation affects job satisfaction among human resource employees in selected government agencies of Palo and Tacloban City, using Social Exchange Theory (SET) as a framework. A convergent parallel mixed-method approach was employed, combining key informant interviews with HR managers and survey questionnaires with HR employees. The findings reveal that E-HRM implementation enhances job satisfaction primarily by strengthening employee perception of organizational support (POS) and the quality of their relationships with supervisors (LMX). When POS and LMS are accounted for, the direct impact of E-HRM on job satisfaction becomes insignificant, emphasizing the crucial role of these mediating factors. This suggests that implementing E-HRM systems is not enough-organizations should also focus on fostering supportive environments and strong supervisor-employee relationships to maximize job satisfaction. Strengthening these social dynamics not only improves employee morale but also enhances the overall effectiveness of digital HR initiatives. Agencies that invest in both technological improvements and relationship-building are more likely to see lasting benefits from E-HRM adoption. As the public sector continues to modernize, a holistic approach that addresses both system functionality and employee experience will be key to sustaining engagement and achieving strategic HR goals.